Given f(x) = 3x - 1 and g(x)= -x + 6, find f(-2) + g(5)

Question

Asked 6/24/2013 8:21:10 AM

Updated 5/26/2014 7:55:51 PM

13 Answers/Comments

This conversation has been flagged as incorrect.

selymi|Points 10716|

bcous05|Points 52|

mythmoh|Points 5349|

scalter|Points 1001|

uxiali|Points 1587|

SarahGCarpio|Points 51|

daddy_ryan|Points 999|

emosara|Points 1294|

Cluvsny|Points 230|

fireandh20|Points 1555|

chamlin|Points 90|

twistedechoes|Points 46|

andrewpallarca|Points 22732|

andrewpallarca|Points 22732|

itolduso|Points 7377|

Question

Asked 6/24/2013 8:21:10 AM

Updated 5/26/2014 7:55:51 PM

13 Answers/Comments

This conversation has been flagged as incorrect.

Rating

3

f(x) = 3x - 1,

f(-2) = 3(-2) - 1 = -6 - 1 = -7.

g(x)= -x + 6,

g(5) = -(5) + 6 = 1.

f(-2) + g(5) = -7 + 1 = -6

f(-2) = 3(-2) - 1 = -6 - 1 = -7.

g(x)= -x + 6,

g(5) = -(5) + 6 = 1.

f(-2) + g(5) = -7 + 1 = -6

Added 5/26/2014 7:31:04 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/26/2014 9:39:02 PM]

3

(3a^2)^3 = 27a^6

Added 5/26/2014 7:31:31 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/26/2014 9:39:12 PM]

3

5(2x -3) + 4( x + 1)

= 10x - 15 + 4x + 4

= 14x - 11

= 10x - 15 + 4x + 4

= 14x - 11

Added 5/26/2014 7:32:20 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/26/2014 9:39:23 PM]

3

5(x + y) + 3(x - y)

= 5x + 5y + 3x - 3y

= 8x + 2y

= 5x + 5y + 3x - 3y

= 8x + 2y

Added 5/26/2014 7:33:13 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/26/2014 9:40:52 PM]

3

f(x) = x² + 5x,

f(-2) = (-2)² + 5(-2) = 4 - 10 = -6

f(-2) = (-2)² + 5(-2) = 4 - 10 = -6

Added 5/26/2014 7:34:14 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/26/2014 9:41:10 PM]

3

g(x) = 2x + 1

g(3) = 2(3) + 1 = 6 + 1 = 7

g(3) = 2(3) + 1 = 6 + 1 = 7

Added 5/26/2014 7:35:02 PM

3

g(x)=2x + 1,

g(a + h)- g(a) = [2(a + h) + 1] - (2a + 1)

= 2a + 2h + 1 - 2a - 1

= 2h

g(a + h)- g(a) = [2(a + h) + 1] - (2a + 1)

= 2a + 2h + 1 - 2a - 1

= 2h

Added 5/26/2014 7:43:57 PM

3

5(x - 2) + 3x

= 5x - 10 + 3x

= 8x - 10

= 5x - 10 + 3x

= 8x - 10

Added 5/26/2014 7:44:43 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/26/2014 9:41:15 PM]

3

3(x + 2) + 4(x - 5)

= 3x + 6 + 4x - 20

= 7x - 14

= 3x + 6 + 4x - 20

= 7x - 14

Added 5/26/2014 7:47:04 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/26/2014 9:41:25 PM]

3

6 - 2(-1) + | -5 | = 6 + 2 + 5 = 8 + 5 = 13

Added 5/26/2014 7:54:29 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/26/2014 9:44:21 PM]

3

6(-3) - | -5 | + | 3 | = -18 - 5 + 3 = -23 + 3 = -20

Added 5/26/2014 7:55:13 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/26/2014 9:44:22 PM]

3

12÷3·(-3) + |-8|= 4(-3) + 8 = -12 + 8 = -4

Added 5/26/2014 7:55:51 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/26/2014 9:44:37 PM]

29,533,862

questions answered

There are no comments.